Оценка влияния шоков на российский фондовый рынок с помощью R - Никита Олегович Иванов; Валерий Владимирович Давнис (Современная экономика: проблемы и решения, 2016)
Purpose: explore how political (local conflicts) and economical (sanctions imposed by US and Europe governments) shocks affect local financial market “Risk – Return” curve. Discussion:  we use Modern portfolio theory to build “before shock  Risk – Return curve” and “after shock Risk- Return curve”. For the “before shock” period we use securities prices from 31 Dec 2011 to 31 Dec 2013. “After shock” period is defined from 31 Dec 2013 to 31 Dec 2015. We then compare two curves and summarize our results. Results: we see that “after shock Risk – Return curve” lies righter than the “before shock” one. We observe growth in risk in recent 2 years. Finally, we see that in the “after shock” period investors could gain returns that they couldn’t reach in the “before shock’ period.